Stability studies of PbS sensitised TiO2 nanotube arrays for visible light photocatalytic applications by X-ray photoelectron spectroscopy (XPS). (February 2016) - Rahna, N.B.; Kalarivalappil, Vijila; Nageri, Manoj; Pillai, Suresh C.; Hinder, Steven J.; Kumar, V.; Vijayan, Baiju K.
Abstract: Titania nanotube array sensitised with lead sulphide (PbS) were synthesised using a successive ionic layer adsorption and reaction (SILAR) method. The PbS sensitation gives visible light sensitivity to the titania nanotube arrays. The PbS sensitised titania nanotube were characterised using X-ray diffraction, UV–visible spectroscopy and scanning electron microscopy. The stability of the PbS sensitised titania nanotube were monitored through the X-ray photoelectron spectroscopy (XPS). The photocatalytic activity of the titania sensitised with PbS were studied by monitoring the degradation of methylene blue under visible light irradiation. The photocatalytic activity and solar cell efficiency is found to be highly depended on the number of SILAR cycle used for the sensitisation of PbS on titania nanotube. The sample coated for 3 SILAR cycle of PbS shows highest solar cell efficiency and photocatalytic activity under visible light. The photocatalytic activity drastically decreased in the samples after the Ist cycle of photocatalytic reaction. The drastic decrease in the photoactivity is due to the dissolution of PbS nanoparticle on the surface of titania nanotube after the first cycle of photocatalytic reaction. XPS was employed as a tool to probe the dissolution of PbS nanoparticles.